In God We Trust: Romanian-American Religious Interferences in the Twentieth Century - BILIUȚĂ, Ionuț (Presa Universitară Clujeană, 2025)
Throughout the twentieth century, the United States–Romania relationship on various levels was deeply contested on both sides of the Atlantic, and remained unclear, underexplored, and often neglected in scholarly research. The challenges posed by Romania’s geographical position across the Atlantic in Eastern Europe and its shifting political regimes over the past century, from a quasi-democracy during the interwar period to a totalitarian dictatorship during communist years, have significantly shaped the trajectory of diplomatic, economic, cultural, and religious encounters between Americans and Romanians. One of the most overlooked dimensions of U.S.-Romanian relations involved the religious interconnections among churches, splinter groups, communities, and individuals on both sides of the Atlantic, but also how the United States diplomatic structures in post-Wilsonian Europe instrumentalized these religious connections in the benefit of US interests on the European continent, especially from 1920s onwards.